Emergency Department and Radiological Cost of Delayed Diagnosis of Cannabinoid Hyperemesis. (1st January 2019) - Zimmer, David I.; McCauley, Ross; Konanki, Varun; Dynako, Joseph; Zackariya, Nuha; Shariff, Faadil; Miller, Joseph; Binz, Sophia; Walsh, Mark
Abstract : Background. Chronic cannabis use has become prevalent with decriminalization, medical prescription, and recreational legalization in numerous US states. With this increasing incidence of chronic cannabis use a new clinical syndrome has become apparent in emergency departments and hospitals across the country, termed Cannabinoid Hyperemesis (CH). CH has been described as cyclical vomiting and abdominal pain in the setting of chronic cannabis use, which is often temporarily relieved by hot showers. CH presents a diagnostic challenge to clinicians who do not have a high clinical suspicion for the syndrome and can result in high costs and resource utilization for hospitals and patients. This study investigates the expenditures associated with delayed CH evaluation and delayed diagnosis. Methods. This is a retrospective observational study of 17 patients diagnosed with CH at three medical centers in the United States from 2010 to 2015, consisting of two academic centers and a community hospital. Emergency department (ED) costs were calculated and analyzed for patients eventually diagnosed with CH. Results . For the 17 patients treated, the total cost for combined ED visits and radiologic evaluations was an average of 76, 920.92 per patient. On average these patients had 17.9 ED visits before the diagnosis of CH was made. Conclusion. CH provides a diagnostic challenge to clinicians without a high suspicion of the syndrome and may become increasingly prevalent with current trends toward cannabis legalization. The diagnosis of CH can be made primarily through a thorough history and physical examination. Awareness of this syndrome can save institutions money, prevent inappropriate utilization of healthcare resources, and save patients from unnecessary diagnostic tests.